A Study of Groundwater Aquifers in Tumbur Village Wer Tamrian District Tanimbar Islands District - Serang, Rudi (Mutiara: Multidiciplinary Scientifict Journal, 2023)
Water is a primary human need that must be met, but as time increases, the rate of population growth means that water needs are increasingly not being met. The geoelectric method is a geophysical method that utilizes electrical properties to interpret the earth's subsurface. The main aim of the geoelectric method is to find the resistivity value of a rock. The higher the resistivity value, the more difficult it is for the rock to carry an electric current, and vice versa. For this reason, one solution to meet the needs of the Lorulun Village community is to search for groundwater aquifers using one of the methods that can be used, the geoelectric resistivity method. The data collection and analysis method used in this research is to conduct a survey at the location to review and see the conditions directly at the research location. Identification To determine the existence of a water-bearing layer at a certain depth, we can use geophysical methods, namely the geoelectric resistivity method, to obtain an overview of the soil layers below the surface. Apart from that, it can also predict the potential for deep and shallow groundwater in the research area. The problem in this research is analyzing deep groundwater sources based on the characteristics and implementation of geoelectric results and the aim of this research is to conduct a survey and design deep groundwater wells based on the characteristics and implementation of geoelectric results in Tumbur Village, Wer Tamrian District. The data is processed based on the apparent resistivity equation, so that the apparent resistivity value (ρa) is obtained by entering the values ∆V, I, a, and K into the Microsoft Excel program. Then processed using RES2DINV software. The water source is at two points, namely geoelectric drilling points 01 and 02, respectively, where the aquifer is found. The casing screen installation process is placed at 3 meters and 12 meters. The use of gravel packs from a depth of 2 to 12.5 meters is to protect the drilled wall hole from landslides and also act as a filter for mud or other materials entering the screen. and with a depth of ± 15 meters, the resistivity shows a brackish water aquifer. This is caused by the influence of seawater intrusion By conducting a survey and designing a deep-ground water well based on the characteristics and implementation of geoelectric results in Tumbur Village, Wer Tamrian District,